Person Centered Therapy: Salah Satu Pendekatan untuk Mengatasi Kesulitan Pengambilan Keputusan Karier - Purba, Novia; Monika, Sesilia; Kastanya, Lidia; Sumbaga, Marchelina Febe; Fellicya, Fellicya; Haryadi, Audreynadhine (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2025)
Career decision-making is a crucial phase in adolescents’ lives, often marked by confusion and a lack of self-understanding. This study aims to explore the effectiveness of Person-Centered Therapy (PCT) in assisting high school students in identifying their interests, talents, and making appropriate career decisions. A qualitative case study approach was employed, focusing on a student, referred to as AD, who struggled with career decision-making despite strong academic performance. The intervention consisted of three individual counseling sessions based on the PCT approach, integrated with Gelatt’s five-step decision-making model. Data were collected through interviews, observations, and psychological assessments (graphic, cognitive, and interest tests). The findings revealed a significant improvement in self-awareness, understanding of personal interests, and AD’s self-confidence. Furthermore, the student’s career decision-making difficulty score decreased from a high to a low category. These results indicate that PCT is effective in fostering autonomy, clarifying self-identity, and facilitating more accurate career decisions. Although limited to a single participant, this study contributes to the development of more humanistic guidance strategies in school settings